Mitigation of salt stress in Sorghum bicolor L. by the halotolerant endophyte Pseudomonas stutzeri ISE12 - Rajabi Dehnavi, Ahmad; Piernik, Agnieszka; Ludwiczak, Agnieszka; Szymańska, Sonia; Ciarkowska, Anna; Cárdenas Pérez, Stefany; Hrynkiewicz, Katarzyna (Frontiers in Plant Science, 2024)
Increasing soil salinity, exacerbated by climate change, threatens seed germination and crop growth, causing significant agricultural losses. Using bioinoculants based on halotolerant plant growth-promoting endophytes (PGPEs) in modern agriculture is the most promising and sustainable method for supporting plant growth under salt-stress conditions. Our study evaluated the efficacy of Pseudomonas stutzeri ISE12, an endophyte derived from the extreme halophyte Salicornia europaea, in enhancing the salinity tolerance of sorghum (Sorghum bicolor L.). We hypothesized that P. stutzeri ISE12 would improve sorghum salt tolerance to salinity, with the extent of the increase in tolerance depending on the genotype's sensitivity to salt stress. Experiments were conducted for two sorghum genotypes differing in salinity tolerance (Pegah - salt tolerant, and Payam - salt sensitive), which were inoculated with a selected bacterium at different salinity concentrations (0, 100, 150, and 200 mM NaCl). For germination, we measured germination percentage and index, mean germination time, vigour, shoot and root length of seedlings, and fresh and dry weight. In pot experiments, we assessed the number of leaves, leaf area, specific leaf area, leaf weight ratio, relative root weight, plantlet shoot and root length, fresh and dry weight, proline and hydrogen peroxide concentrations, and peroxidase enzyme activity. Our study demonstrated that inoculation significantly enhanced germination and growth for both sorghum genotypes. The salinity-sensitive genotype (Payam) responded better to bacterial inoculation during germination and early seedling growth stages, showing approximately 1.4 to 1.8 times greater improvement than the salinity-tolerant genotype (Pegah). Payam also displayed better performance at the plantlet growth stage, between 1.1 and 2.6 times higher than Pegah. Furthermore, inoculation significantly reduced hydrogen peroxide, peroxidase activity, and proline levels in both sorghum genotypes. These reductions were notably more pronounced in Payam, with up to 1.5, 1.3, and 1.5 times greater reductions than in Pegah. These results highlight the efficacy of P. stutzeri ISE12 in alleviating oxidative stress and reducing energy expenditure on defense mechanisms in sorghum, particularly benefiting salt-sensitive genotypes. Our findings highlight the potential of the bacterial endophyte P. stutzeri ISE12 as a valuable bioinoculant to promote sorghum growth under saline conditions.